Experimental study on a hybrid battery thermal management system combining oscillating heat pipe and liquid cooling - Hongkun, Lu; Muhamad, Mat Noor; Kadirgama, Kumaran (Global Digital Central, 2024)
To improve the thermal performance and temperature uniformity of battery pack, this paper presents a novel battery thermal management system (BTMS) that integrates oscillating heat pipe (OHP) technology with liquid cooling. The primary innovation of the new hybrid BTMS lies in the use of an OHP with vertically arranged evaporator and condenser, enabling dual heat transfer pathways through liquid cooling plate and OHP.This study experimentally investigates the performance characteristics of the ⊥-shaped OHP and hybrid BTMS. Results show that lower filling ratios significantly enhance the OHP’s startup performance but reduce operational stability, with optimal performance achieved at a 26.1% filling ratio. Acetone, as a single working fluid, exhibited superior heat transfer performance under low-load conditions compared to mixed fluids, while the acetone/ethanol mixture, forming a non-azeotropic solution, minimized temperature fluctuations. At 100 W, the ⊥-shaped OHP with a horizontally arranged evaporator demonstrated better heat transfer performance than 2D-OHP designs. Compared to a liquidBTMSusingwater coolant at 280W, the hybridBTMS reduced the equivalent thermal resistance (RBTMS) and maximum temperature difference (ΔTmax) by 8.06% and 19.1%, respectively. When graphene nanofluid was used as the coolant in hybrid BTMS, the battery pack’s average temperature (Tb) dropped from 52.2°C to 47.9°C, with RBTMS andΔTmax decreasing by 20.1% and 32.7%, respectively. These findings underscore the hybrid BTMS’s suitability for high heat load applications, offering a promising solution for electric vehicle thermal management.